Prevalence of Sleep Disturbances in Pediatric Cancer Patients and Their Diagnosis and Management - Irtiza N. Sheikh; Michael Roth; Peter L. Stavinoha (MDPI AG, 2021)
Sleep disturbances represent an understudied yet common source of distress among pediatric cancer patients and survivors, with deleterious effects on quality of life. Sleep issues stem from multiple risk factors, yet individual contributors are difficult to isolate, consequently impeding the identification of targets for intervention. In many pediatric cancer patients, disrupted sleep and its negative impact on quality of life continue into adulthood and may affect various functional domains. This literature review highlights the types and prevalence of sleep disturbances in pediatric cancer patients during active treatment and through survivorship. Potential etiological and risk factors for disturbed sleep are summarized, including the effects of cancer and its treatment, psychosocial and family factors, as well as individual-patient aspects, such as genetics, mood and coping skills. While existing assessment and management strategies are reviewed, the literature is incomplete, and significant gaps emerge in our understanding of sleep disturbances in pediatric cancer patients and survivors. The review concludes with recommendations of areas where further research is needed. The aims of this review include increasing clinicians' awareness of sleep disturbances as a significant source of poor quality of life in pediatric cancer patients and survivors and directing researchers to gaps in our understanding of sleep disturbances in pediatric cancer patients and survivors.